Pediatric training and practice of Canadian chiropractic and naturopathic doctors: a 2004–2014 comparative study - Antony Porcino; Leslie Solomonian; Stephen Zylich; Brian Gluvic; Chantal Doucet; Sunita Vohra (BMC Complementary and Alternative Medicine, 2017)
Abstract Background To assess chiropractic (DC) and naturopathic doctors’ (ND) knowledge, attitudes, and behaviour with respect to the pediatric patients in their practice. Methods Cross-sectional surveys were developed in collaboration with DC and ND educators. Surveys were sent to randomly selected DCs and NDs in Ontario, Canada in 2004, and a national online survey was conducted in 2014. Data were analyzed using descriptive statistics, t-tests, non-parametric tests, and linear regression. Results Response rates for DCs were n = 172 (34%) in 2004, n = 553 (15.5%) in 2014, and for NDs, n = 171 (36%) in 2004, n = 162 (7%) in 2014. In 2014, 366 (78.4%) of DCs and 83 (61%) of NDs saw one or more pediatric patients per week. Pediatric training was rated as inadequate by most respondents in both 2004 and 2014, with most respondents (n = 643, 89.9%) seeking post-graduate training by 2014. Respondents’ comfort in treating children and youth is based on experience and post-graduate training. Both DCs and NDs that see children and youth in their practices address a broad array of pediatric health concerns, from well child care and preventative health, to mild and serious illness. Conclusions Although the response rate in 2014 is low, the concerns identified a decade earlier remain. The majority of responding DCs and NDs see infants, children, and youth for a variety of health conditions and issues, but self-assess their undergraduate pediatric training as inadequate. We encourage augmented pediatric educational content be included as core curriculum for DCs and NDs and suggest collaboration with institutions/organizations with expertise in pediatric education to facilitate curriculum development, especially in areas that affect patient safety.